Coronavirus, domestic labour and care: Gendered roles locked down - Craig, Lyn (Journal of Sociology, 2020)
The Covid-19 pandemic turned daily lives upside down. Lockdowns and physical distancing meant hundreds of thousands of people switched to working from home, significantly blurring the temporal and spatial boundaries between paid work, domestic labour and caring for others. This article explores gender relations, and the division of employment, domestic labour and care, drawing on early results from an online survey, Work and Care in the Time of Covid-19, carried out between 7 May and 4 June 2020.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; australie; care; covid-19; discipline; division sexuelle du travail; océanie; pandémie; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail de reproduction; travail invisible

Rethinking social reproduction in the time of COVID-19 - Dattani, Kavita (The Journal of Australian Political Economy, 2020)
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; care; covid-19; discipline; genre; géographie; périodes historiques; ressource en ligne; sciences humaines; thématiques; travail; travail domestique; violences

Comment la crise fait-elle ressortir les inégalités de genre ? - Plumauzille, Clyde (2020)
Aides-soignantes, caissières, aides à domicile… ce sont majoritairement des femmes qui se retrouvent en première ligne contre le virus. Comme le rappelle l’historienne Clyde Plumauzille dans ce podcast, ces inégalités ne sont pas nouvelles, la prise en charge d’autrui au sein du foyer ou dans la société étant historiquement dévolue aux femmes.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; charge mentale; confinement; covid-19; histoire et politique; hétérosexisme; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; travail; travail domestique; violences; violences conjugales

The COVID-19 pandemic has increased the care burden of women and families - Power, Kate (Sustainability: Science, Practice and Policy, 2020)
While women were already doing most of the world’s unpaid care work prior to the onset of the COVID-19 pandemic, emerging research suggests that the crisis and its subsequent shutdown response have resulted in a dramatic increase in this burden. It is likely that the negative impacts for women and families will last for years without proactive interventions. What we commonly refer to as “the economy” would not function without the (often unrecognized) foundation of work provided by the “care economy”: the reproduction of everyday life through cooking, raising children, and so forth. The paid economy has slowed not only because people are physically not allowed into workplaces, but also because many families currently need to raise and educate their children without institutional support, which is reducing remunerated working hours and increasing stress. It has long been recognized that gross domestic product ignores the care economy and heterodox economists have promoted alternative economic systems that could value care work and facilitate a fairer sharing of domestic labor while promoting environmental and economic sustainability. This policy brief builds on recent work on the care economy to explore implications of the COVID-19 pandemic and opportunities for addressing the burden of unpaid care work.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; care; covid-19; famille; genre; périodes historiques; ressource en ligne; thématiques; travail